The Effectiveness of English-Subtitled Videos in Enhancing Speaking, Listening and Vocabulary Skills: A Meta-Analysis - Oktapiani, Ita Usmi; Ilham, Ilham; Humaira, Humaira; Bafadal, Fauzi; Adebayo, Mosunmola; Fasih, Parima (Journal of Languages and Language Teaching, 2024)
English-subtitled videos are a popular and accessible form of multimedia that can enhance language learning by providing authentic input and scaffolding comprehension. Therefore, This study aims to assess the effectiveness of English-subtitled videos as a learning tool for enhancing speaking, listening, and vocabulary skills among language learners. A total of 87 eligible studies were included in the analysis. The results of our analysis, conducted using JASP software simulation, indicate a statistically significant impact of English-subtitled videos on language learning, accounting for 59% of the variance, placing it in the Moderate category of significance. Specifically, the effect size values for speaking, listening, and vocabulary were 0.64, 0.59, and 0.55, respectively, highlighting their positive influence. Furthermore, the present research revealed that studies published in 2022 exhibited the highest effect size, with an estimated value of 0.771, underscoring the growing relevance of this instructional approach in recent years. Additionally, when considering the number of participants, studies with fewer than 40 participants demonstrated the highest effect, with an estimated value of 0.534. This suggests that English-subtitled videos are particularly well-suited for improving speaking skills, especially in smaller sample sizes. These findings offer valuable insights for educators and learners seeking effective multimedia tools to develop language proficiency.